Kompetencje geometryczne nauczycieli matematyki - Czajkowska, Monika (Annales Universitatis Paedagogicae Cracoviensis | Studia ad Didacticam Mathematicae Pertinentia, 2017)
Practice proves that students tend to face difficulties in learninggeometry. This observation is partially confirmed by the results of educationalresearch as well as external exams. It happens repeatedly that studentsget lower marks in arithmetic or algebra tasks. The causes of such situationare complex. One of the reasons is that teaching geometry requires specialteaching skills characteristic for this specific teaching branch as well as theneed for “specific vision”. Therefore, I decided to study the geometric skillsof mathematics teachers more carefully. For this purpose, I made use of tworesearch results: international research TEDS-M 2008 as well as nationwideresearch The research of needs the elementary education teachers as well asmathematics teachers have in the scope of their professional development.This article presents the results of the analysis together with my personalthoughts on education and improvement of teachers’ skills in the area of geometry.